PSYCHOLOGICAL, ECONOMIC AND BEHAVIORAL DETERMINANTS OF WILLINGNESS TO PAY FOR FITNESS PROGRAMS AMONG GENERATION Z - Aleksić, Ivana; Grujić, Stefan (Economic Outlook, 2026)
Consumer behavior in contemporary conditions is characterized by the complex influence of economic, psychological, and digital factors that shape purchasing decisions and the willingness to pay for certain products and services. The subject of this research is the analysis of factors influencing the willingness of Generation Z members to pay for fitness programs, with a particular focus on psychological, economic, socio-cultural, and digital determinants of consumer behavior. The aim of the study is to identify and explain the key factors determining willingness to pay (WTP) in the context of fitness services. The research hypotheses relate to the influence of life satisfaction, motivation, health status, income, price sensitivity, customer experience, loyalty, digital channels, as well as the influence of family and influencers on WTP. The study employed descriptive statistics, correlation analysis, and multiple regression analysis. The results indicate that willingness to pay is significantly influenced by user experience, price perception, motivation, income, and influencer impact, while some factors, such as loyalty and digital channels, lost significance in the multivariate model. The research confirms that WTP is the result of a complex interaction of multiple groups of factors and that the digital environment and experiential aspects are becoming increasingly important in shaping consumer decisions.